Cerebrospinal Fluid Norepinephrine and Neurocognition in HIV and Methamphetamine Dependence. (1st October 2020) - Saloner, Rowan; Cherner, Mariana; Iudicello, Jennifer E.; Heaton, Robert K.; Letendre, Scott L.; Ellis, Ronald J.
Abstract : Objective: HIV disease and methamphetamine (METH) dependence share overlapping mechanisms of neurotoxicity that preferentially compromise monoamine-rich frontostriatal circuitry. However, norepinephrine (NE) function is poorly understood in HIV and METH dependence. We evaluated associations between cerebrospinal fluid (CSF) NE and HIV, METH dependence, and neurocognition. Methods: Participants included 125 adults, stratified by HIV serostatus (HIV+/HIV−) and recent METH dependence (METH+/METH−), who underwent comprehensive neurocognitive testing and lumbar puncture. CSF NE was assayed using high-performance liquid chromatography. Multivariable regression modelled NE as a function of HIV, METH, and their interaction, adjusting for demographic and clinical factors. Pearson correlations examined relationships between NE and demographically-adjusted neurocognitive domain scores. Results: HIV significantly interacted with METH ( P < 0.001) such that compared with HIV−/METH−, CSF NE was markedly elevated in the single risk-groups (HIV+/METH−: d = 0.96; HIV−/METH+: d = 0.79) and modestly elevated in the dual-risk group (HIV+/METH+: d = 0.48). This interaction remained significant after adjustment for lifetime depression, antidepressant use, and race/ethnicity. In the full sample, higher NE levels significantly correlated with worse global function ( r = −0.19), learning ( r = −0.23), and delayed recall ( r = −0.18). Similar relationships between higher NE and worse neurocognition were detected in the METH− groups (ie, HIV−/METH− and HIV+/METH−) and in the virally-suppressed persons HIV+ subgroup, but not in the METH+ groups (ie, HIV−/METH+, HIV+/METH+). Discussion: HIV and METH independently, but not additively, relate to noradrenergic excess in the central nervous system, and perturbations to noradrenergic function may represent a pathophysiological mechanism of HIV-related neurocognitive dysfunction. Consistent with prior reports that noradrenergic excess compromises hippocampal and prefrontal function, higher NE related to worse neurocognition, even among successfully treated persons with HIV. Pharmacological and psychosocial interventions that stabilize NE function may improve neurocognition in persons with HIV.